Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 132410 by bramlexs22 last updated on 14/Feb/21

 ∫_0 ^( ∞)  (dx/((x^4 −x^2 +1)^2 ))

0dx(x4x2+1)2

Answered by EDWIN88 last updated on 14/Feb/21

I=∫_0 ^∞  (dx/((x^4 −x^2 +1))) ; replace x by (1/x)  I=∫_∞ ^0  (((−(1/x^2 ))/(((1/x^4 )−(1/x^2 )+1)^2 )))dx=∫_0 ^∞ ((x^6  dx)/((x^4 −x^2 +1)^2 ))  2I=∫_0 ^∞  ((x^6 +1)/((x^4 −x^2 +1)^2 ))dx ; Q(x)=(x^4 −x^2 +1)^2   Q′(x)=2(4x^3 −2x)(x^4 −x^2 +1)  gcd Q′(x) and Q(x) is Q_1 (x)=x^4 −x^2 +1  and Q_2 (x)=((Q(x))/(Q_1 (x)))= x^4 −x^2 +1  I=(1/2)∫((x^6 +1)/((x^4 −x^2 +1)^2 )) dx = (1/2){ [((ax^3 +bx^2 +cx+d)/(x^4 −x^2 +1)) ]+∫ ((ex^3 +fx^2 +gx+h)/(x^4 −x^2 +1)) dx }  differentiating both sides and solving   for coefficients

I=0dx(x4x2+1);replacexby1xI=0(1x2(1x41x2+1)2)dx=0x6dx(x4x2+1)22I=0x6+1(x4x2+1)2dx;Q(x)=(x4x2+1)2Q(x)=2(4x32x)(x4x2+1)gcdQ(x)andQ(x)isQ1(x)=x4x2+1andQ2(x)=Q(x)Q1(x)=x4x2+1I=12x6+1(x4x2+1)2dx=12{[ax3+bx2+cx+dx4x2+1]+ex3+fx2+gx+hx4x2+1dx}differentiatingbothsidesandsolvingforcoefficients

Answered by Lordose last updated on 14/Feb/21

  Ω = ∫_0 ^( ∞) (1/((x^4 −x^2 +1)^2 ))dx = ∫_0 ^( ∞) (((1+x^2 )^2 )/((1+x^6 )^2 ))dx  Ω = ∫_0 ^( ∞) (1/((1+x^6 )^2 ))dx + ∫_0 ^( ∞) ((2x^2 )/((1+x^6 )^2 ))dx + ∫_0 ^( ∞) (x^4 /((1+x^6 )^2 ))dx  Ω =^(x=u^(1/6) ) (1/6)(∫_0 ^( ∞) (u^((1/6)−1) /((1+u)^2 ))du + 2∫_0 ^( ∞) (u^((1/3)+(1/6)−1) /((1+u)^2 )) + ∫_0 ^( ∞) (u^((2/3)+(1/6)−1) /((1+u)^2 ))du)  Ω = (1/6)(𝛃((1/6),((11)/6)) + 2𝛃((1/2),(3/2)) + 𝛃((5/6),(7/6)))

Ω=01(x4x2+1)2dx=0(1+x2)2(1+x6)2dxΩ=01(1+x6)2dx+02x2(1+x6)2dx+0x4(1+x6)2dxΩ=x=u1616(0u161(1+u)2du+20u13+161(1+u)2+0u23+161(1+u)2du)Ω=16(β(16,116)+2β(12,32)+β(56,76))

Answered by Dwaipayan Shikari last updated on 14/Feb/21

∫_0 ^∞ (((x^2 +1)^2 )/((x^6 +1)^2 ))dx=∫_0 ^∞ (x^4 /((x^6 +1)^2 ))dx+((2x^2 )/((x^6 +1)^2 ))+(1/((x^6 +1)^2 ))dx    x^6 =u  =(1/6)∫_0 ^∞ (u^(−(1/6)) /((u+1)^2 ))du+(1/3)∫_0 ^∞ (u^(−(1/2)) /((u+1)^2 ))+(1/6)∫_0 ^∞ (u^(−(5/(6 ))    ) /((u+1)^2 ))du  =(1/6)∫_0 ^∞ (u^((5/6)−1) /((u+1)^((7/6)+(5/6)) ))+(1/3)∫_0 ^∞ (u^((1/2)−1) /((u+1)^((3/2)+(1/2)) ))+(1/6)∫_0 ^∞ (u^((1/6)−1) /((u+1)^((1/6)+((11)/6)) ))du  =(1/6).((Γ((5/6))Γ((7/6)))/(Γ(2)))+(1/3).((Γ((1/2))Γ((3/2)))/(Γ(2)))+(1/6).((Γ((1/6))Γ(((11)/6)))/(Γ(2)))  =(π/(18))+(π/6)+((5π)/(18))=(π/2)

0(x2+1)2(x6+1)2dx=0x4(x6+1)2dx+2x2(x6+1)2+1(x6+1)2dxx6=u=160u16(u+1)2du+130u12(u+1)2+160u56(u+1)2du=160u561(u+1)76+56+130u121(u+1)32+12+160u161(u+1)16+116du=16.Γ(56)Γ(76)Γ(2)+13.Γ(12)Γ(32)Γ(2)+16.Γ(16)Γ(116)Γ(2)=π18+π6+5π18=π2

Answered by mathmax by abdo last updated on 14/Feb/21

I=∫_0 ^∞   (dx/((x^4 −x^2 +1)^2 )) ⇒2I=∫_(−∞) ^(+∞)  (dx/((x^4 −x^2  +1)^2 ))  ϕ(z)=(1/((z^4 −z^2 +1)^2 )) poles of ϕ!  z^4 −z^2 +1=0 ⇒u^2 −u+1=0(u=z^2 )  Δ=−3 ⇒u_1 =((1+i(√3))/2) =e^((iπ)/3)  and u_2 =e^(−((iπ)/3))  ⇒  z^4 −z^2 +1 =(z^2 −e^((iπ)/3) )(z^2 −e^(−((iπ)/3)) ) ⇒ϕ(z)=(1/((z^2 −e^((iπ)/3) )^2 (z^2 −e^(−((iπ)/3)) )^2 ))  =(1/((z−e^((iπ)/6) )^2 (z+e^((iπ)/6) )^2 (z−e^(−((iπ)/6)) )^2 (z+e^(−((iπ)/6)) )^2 ))  the poles of ϕ are +^− e^((iπ)/6)  and +^− e^(−((iπ)/6))   (doubles)  ∫_(−∞) ^(+∞)  ϕ(z)dz =2iπ{ Res(ϕ,e^((iπ)/6) )+Res(ϕ,−e^(−((iπ)/6)) )}  Res(ϕ,e^((iπ)/6) )=lim_(z→e^((iπ)/6) )   (1/((2−1)!)){(z−e^((iπ)/6) )^2 ϕ(z)}^((1))   =lim_(z→e^((iπ)/6) )    {(1/((z+e^((iπ)/6) )^2 (z^2 −e^(−((iπ)/3)) )))}^((1))   =lim_(z→e^((iπ)/6) )    −((2(z+e^((iπ)/6) )(z^2 −e^(−((iπ)/3)) )+2z(z+e^((iπ)/6) )^2 )/((z+e^((iπ)/6) )^4 (z^2 −e^(−((iπ)/3)) )^4 ))  =−lim_(z→e^((iπ)/6) )  (2/((z+e^((iπ)/6) )^3 (z^2 −e^(−((iπ)/3)) )^3 )) +((2z)/((z+e^((iπ)/6) )^2 (z^2 −e^(−((iπ)/3)) )^4 ))  =−{(2/((2e^((iπ)/3) )^3 (2isin((π/3)))^3 )) +((2e^((iπ)/6) )/((2e^((iπ)/6) )^2 (2isin((π/3)))^4 ))}  =−{(2/(8(−1)(−8i)(((√3)/2))^3 )) +((2e^((iπ)/6) )/(4e^((iπ)/3) .16(((√3)/2))^4 ))}....be continued...

I=0dx(x4x2+1)22I=+dx(x4x2+1)2φ(z)=1(z4z2+1)2polesofφ!z4z2+1=0u2u+1=0(u=z2)Δ=3u1=1+i32=eiπ3andu2=eiπ3z4z2+1=(z2eiπ3)(z2eiπ3)φ(z)=1(z2eiπ3)2(z2eiπ3)2=1(zeiπ6)2(z+eiπ6)2(zeiπ6)2(z+eiπ6)2thepolesofφare+eiπ6and+eiπ6(doubles)+φ(z)dz=2iπ{Res(φ,eiπ6)+Res(φ,eiπ6)}Res(φ,eiπ6)=limzeiπ61(21)!{(zeiπ6)2φ(z)}(1)=limzeiπ6{1(z+eiπ6)2(z2eiπ3)}(1)=limzeiπ62(z+eiπ6)(z2eiπ3)+2z(z+eiπ6)2(z+eiπ6)4(z2eiπ3)4=limzeiπ62(z+eiπ6)3(z2eiπ3)3+2z(z+eiπ6)2(z2eiπ3)4={2(2eiπ3)3(2isin(π3))3+2eiπ6(2eiπ6)2(2isin(π3))4}={28(1)(8i)(32)3+2eiπ64eiπ3.16(32)4}....becontinued...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com